'A Rose by Any Other Name Would Smell as Sweet': Finding Beauty in the Past Century. (5th September 2019) - Powers, Alan
Abstract: Were ideas of beauty denied by modern architects, only to re‐emerge recently? Alan Powers, teacher of architectural history at the London School of Architecture, University of Westminster and New York University in London, looks at notions of beauty and its synonyms during the halcyon days of 20th‐century Modernism.